2017
DOI: 10.4238/gmr16019404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of propolis ethanol extract on myostatin gene expression and muscle morphometry of Nile tilapia in net cages

Abstract: ABSTRACT. Propolis can be used as growth enhancer due to its antimicrobial, antioxidant, and immune-stimulant properties, but its effects on morphometry and muscle gene expression are largely unknown. The present study evaluates the influence of propolis on muscle morphometry and myostatin gene expression in Nile tilapia (Oreochromis niloticus) bred in net cages. Reversed males (GIFT strain) with an initial weight of 170 ± 25 g were distributed in a (2 x 4) factorial 2 E.L. Buck et al.Genetics and Molecular Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…The mean temperature of the water during the experimental period was compatible with the thermal comfort zone of Nile tilapia [6], and was similar to that in a previous experiment conducted in Rio do Corvo [4]. The zootechnical indexes of tilapia did not differ significantly between treatments (p > 0.05), and the final weight was consistent with the slaughter weight of this species when farmed in net cages.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…The mean temperature of the water during the experimental period was compatible with the thermal comfort zone of Nile tilapia [6], and was similar to that in a previous experiment conducted in Rio do Corvo [4]. The zootechnical indexes of tilapia did not differ significantly between treatments (p > 0.05), and the final weight was consistent with the slaughter weight of this species when farmed in net cages.…”
Section: Discussionsupporting
confidence: 76%
“…In Brazil, the production of this species represented approximately half of all aquaculture production in 2017, which was approximately 559 thousand tons [2]. However, due to the rapid expansion and intensification of Nile tilapia production, the high densities adopted in farming systems have become a challenge, since they are a stress factor for the fish that can cause economic losses [3][4][5].…”
Section: Introductionmentioning
confidence: 99%
“…These values were compatible with the optimal water quality parameters of Nile tilapia [36], and were similar to those previously reported in Nile Tilapia, Oreochromis niloticus [37] fed Azolla-based-diets in earthen ponds. In addition, the pH, alkalinity, hardness and nitrate (NO 3 -N) values were significantly higher (p< 0.05) in test diet compared to the control.…”
Section: Page 4 Of 11supporting
confidence: 91%
“…were used to evaluate the effect of bee products on skeletal muscle. The effects of bee products on muscle mass varied considerably: some studies reported that bee products increased muscle mass [ 36 , 54 , 90 , 96 , 100 , 105 , 113 ] and improved physical performance [ 95 , 96 , 97 , 98 , 99 ] while others could not or did not depict any significant change in muscle mass [ 38 , 102 , 103 , 104 , 110 , 117 ]. However, the latter revealed major beneficial effects related to the biology of skeletal muscle aging such as improved muscle protein deposition [ 104 ], enhanced activity of mitochondrial enzymes [ 106 ], decreased muscle infiltration by inflammatory cells, decreased muscle proteolysis, lowered lipid peroxidation and protein carbonylation [ 102 , 103 ], increased microvascular blood supply, heightened production of antioxidants [ 110 ], and increased clearance of AGEs from skeletal muscle [ 38 ].…”
Section: Discussionmentioning
confidence: 99%